Institutional Constraints in Local Bureaucratic Reform: Evidence from Konawe Selatan Regency - Syamsul Alam; Sirajuddin Sirajuddin; Riston. G. Ahmad (NeoRespublica : Jurnal Ilmu Pemerintahan, 2026)
Bureaucratic reform has become a central agenda in public administration, yet implementation outcomes remain uneven, especially in decentralized systems where local governments translate national reform mandates into practice. This article examines how institutional constraints shape bureaucratic reform implementation in Konawe Selatan Regency, Indonesia. Using a qualitative evaluative case study, the analysis draws on documentary evidence from the assessment of the 2015–2019 reform cycle and the formulation of the 2020–2024 bureaucratic reform roadmap, complemented by five semistructured interviews with anonymized key informants (I1–I5) involved in reform coordination, human resource management, performance monitoring, and policy advisory functions. Findings indicate that reform underperformance is driven less by the absence of policy than by interconnected institutional misalignment across four dimensions. Regulative constraints emerged through policy incoherence and limited operational guidance, producing interpretive variation and compliance-driven implementation. Structural constraints reflected fragmented reform machinery and discontinuous coordination, weakening sustainability across staffing changes. Capacity constraints involved limited competence in performance-based management and uneven technological readiness, contributing to the persistence of procedural routines. Political constraints were evident in weak reform ownership and limited leadership innovation, allowing reform to remain a routine administrative agenda rather than a strategic governance priority. The study contributes by reframing local bureaucratic reform failure as an institutional alignment problem rather than a managerial deficiency. Practically, it suggests that local governments should govern reform as a sequenced institutional alignment strategy—strengthening roadmap intelligibility, institutionalizing coordination, prioritizing capability-building, and sustaining political ownership to shift reform from symbolic compliance toward durable governance improvement.